Compensatory functional connectome changes in a rat model of traumatic brain injury. Issue 4 (23rd October 2021) - Yang, Zhihui; Zhu, Tian; Pompilus, Marjory; Fu, Yueqiang; Zhu, Jiepei; Arjona, Kefren; Arja, Rawad Daniel; Grudny, Matteo M; Plant, H Daniel; Bose, Prodip; Wang, Kevin K; Febo, Marcelo
Abstract: Penetrating cortical impact injuries alter neuronal communication beyond the injury epicentre, across regions involved in affective, sensorimotor and cognitive processing. Understanding how traumatic brain injury reorganizes local and brain wide nodal interactions may provide valuable quantitative parameters for monitoring pathological progression and recovery. To this end, we investigated spontaneous fluctuations in the functional MRI signal obtained at 11.1 T in rats sustaining controlled cortical impact and imaged at 2- and 30-days post-injury. Graph theory-based calculations were applied to weighted undirected matrices constructed from 12 879 pairwise correlations between functional MRI signals from 162 regions. Our data indicate that on Days 2 and 30 post-controlled cortical impact there is a significant increase in connectivity strength in nodes located in contralesional cortical, thalamic and basal forebrain areas. Rats imaged on Day 2 post-injury had significantly greater network modularity than controls, with influential nodes (with high eigenvector centrality) contained within the contralesional module and participating less in cross-modular interactions. By Day 30, modularity and cross-modular interactions recover, although a cluster of nodes with low strength and low eigenvector centrality remain in the ipsilateral cortex. Our results suggest that changes in node strength, modularity, eigenvector centrality and participation coefficient track early and late traumatic brain injury effects on brain functional connectivity. We propose that the observed compensatory functional connectivity reorganization in response to controlled cortical impact may be unfavourable to brain wide communication in the early post-injury period. Abstract : Yang et al. used functional magnetic resonance imaging and graph theory analysis in a rat model of traumatic brain injury and report changes in network topology that tracked early and late traumatic brain injury effects on functional connectivity. The observed changes emphasize functional magnetic resonance imaging activity patterns unfavourable to communication in the early post-injury period. Graphical Abstract: